The effect of freezing and storing processes on the suitability of goat milk for the production of ice-cream desserts - Danków R.; Wójtowski J.; Gut A. (Production systems and product quality in sheep and goats, 2001)
Ice-creams made from both fresh, and defrosted milk were tested: immediately after the ice-cream mixture was prepared, after the hardening process, and after 5 weeks of storage. The following parameters were evaluated: acidity (pH), titratable acidity (°SH), percentage of fat and dry matter contents, as well as viscosity and the degree of aeration (fluffiness). Analysis results proved the suitability of defrosted goat milk for ice-cream production. However, ice-creams made from fresh milk received slightly better results in the organoleptic analysis.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)